2017
DOI: 10.1111/zph.12368
|View full text |Cite
|
Sign up to set email alerts
|

Cat scratch disease: U.S. clinicians' experience and knowledge

Abstract: Cat scratch disease (CSD) is a zoonotic infection caused primarily by the bacterium Bartonella henselae. An estimated 12,000 outpatients and 500 inpatients are diagnosed with CSD annually, yet little is known regarding clinician experience with and treatment of CSD in the United States. Questions assessing clinical burden, treatment and prevention of CSD were posed to 3,011 primary care providers (family practitioners, internists, paediatricians and nurse practitioners) during 2014-2015 as part of the annual n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…Similar to findings from 3 previous studies that reported the highest incidences of cat-scratch disease in the southern United States (13,14,30), in our study, most typical (53.0%) and atypical (57.6%) cat-scratch disease cases occurred in patients residing in this region. In addition, a national survey of US healthcare providers found that those in the Pacific and southern regions of the United States were more likely to have been given a diagnosis of cat-scratch disease than in other regions (32). These findings are further supported by studies that have found higher average B. henselae seroprevalences and active bacteremia in pet cats from warmer, more humid climates, including the southern United States (33,34).…”
Section: Discussionmentioning
confidence: 83%
“…Similar to findings from 3 previous studies that reported the highest incidences of cat-scratch disease in the southern United States (13,14,30), in our study, most typical (53.0%) and atypical (57.6%) cat-scratch disease cases occurred in patients residing in this region. In addition, a national survey of US healthcare providers found that those in the Pacific and southern regions of the United States were more likely to have been given a diagnosis of cat-scratch disease than in other regions (32). These findings are further supported by studies that have found higher average B. henselae seroprevalences and active bacteremia in pet cats from warmer, more humid climates, including the southern United States (33,34).…”
Section: Discussionmentioning
confidence: 83%
“…CSD is usually suspected clinically and by culturing of the pathogen, but detection of organisms in lymph nodes by immunofluorescence, molecular techniques including PCR amplification of Bartonella spp. genes have advantages in unclear case [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cat-scratch disease (CSD) is an infectious zoonotic disease, usually benign, caused by Bartonella henselae and B. clarridgeiae [1]. The causative agents are gram-negative coccobacilli whose biological cycles involve an intermediate host (often fleas), that maintain transmission between cats [2]. The infected saliva and nails of cats are the main routes of transmission to the human.…”
Section: Introductionmentioning
confidence: 99%